Pengaruh Kinerja Corporate Social Responsibility (CSR) Terhadap Prediktabilitas Laba pada Perusahaan yang Bergerak di Sektor Barang Konsumsi Dengan Sub Sektor Rokok, Makanan dan Minuman di Indonesia - Veronica Wijaya; Juniarti Juniarti (Business Accounting Review, 2016)
This study aimed to identify and prove the existence of a relationship between the influence of corporate social performance and the level of predictability of earnings. the corporate social responsibility was assessed by using the criteria of the GRI index. leverage and firm size used as control variabels. This research was carried out on a public companies in Indonesia listed in Jakarta Stock Exchange. The results showed that there was no reciprocal relationship between corporate social performance and corporate financial performance but showed that there was positive affect on the predictability leverage corporate profits, while firm size had positive affect on the level of company predictability of earnings.Meanwhile this research had not been able to prove the existence of a positive relationship between CSR and predictability of earnings.